Effect of an Aqueous Garlic Extract on Kidney Damage in an Experimental Model of Sepsis - ŞENER, GÖKSEL; AKBAY, TUĞBA (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Objective: Sepsis is a systemic inflammatory response against pathogens or substances secreted by pathogens. In this study, the potential protective effect of an aqueous garlic extract (AGE) against sepsis-induced kidney injury. Methods: Rats were divided into four groups: control, sepsis, sepsis+AGE-garlic, and sepsis+pretreated garlic. Sepsis was induced using cecal ligation and perforation. An AGE was orally administered to rats in the sepsis+pretreated garlic group at a dose of 250 (mg/kg/day) for 15 days prior to sepsis induction. In rats in the sepsis+garlic group, the AGE was administered at a single dose (250 mg/kg) immediately after sepsis induction. Twelve hours after sepsis induction, all rats were decapitated and kidney tissues were taken. Glutathione (GSH) and malondialdehyde (MDA) levels and superoxide dismutase (SOD), tissue factor (TF), catalase (CAT), and myeloperoxidase (MPO) activities were determined in the kidney issue. Results: Increased MDA levels and MPO activity and decreased GSH level and SOD and CAT activities due to sepsis were reversed by the AGE. TF activity did not change in sepsis. Shortened clot formation time shows increased TF activity. Accordingly, kidney TF activity significantly increased in mice in the pre-treated garlic group. Conclusion: AGE usage should be considered in developing new sepsis treatment strategies in terms of oxidant and antioxidant balance.
Keywords: Sepsis; kidney; aqueous garlic extract; oxidative stress; tissue factor; OXIDATIVE STRESS; CECAL LIGATION; ALLICIN; PARAMETERS; TOXICITY; RADICALS; BLOOD; RATS